From the Field into the Lab: Useful Approaches to Selecting Species Based on Local Knowledge - Andrade-Cetto, Adolfo; Heinrich, Michael (Frontiers in Pharmacology, 2011)
Ethnopharmacological field studies are indispensable for identifying plants that can be selected for their pharmacological effects and chemical composition. Although the subjective interpretation of results by the researcher is crucial, quantitative data analysis is a useful tool to identify the most promising pharmacological plants. It has been stated that such semi-quantitative information increases the likelihood of finding promising ethnopharmacological leads, but so far no critical review has assessed what standards best meet the requirements of biomedical research. Systematic database searches using SCOPUS, Science Direct, Web of Knowledge, Science Citation Index and Medline with the keywords ‘ethnobotany’, ‘ethnopharmacology’, ‘index’ and ‘consensus’ in research from the last five years form the basis of the current analysis, which identifies particularly useful tools like factor of informant consensus, fidelity level, use value and relative importance. A key feature for further field studies is that they should provide clear information on a range of topics like; detailed data of the importance of these resources within a culture, data of the uses of the species, how and where the plants are collected, drying and storage processes, preparation method, used doses and administration In addition, they must include a collection of records about how the people feel after the plant use, disappearance of specific symptoms and possible side effects.